Sheath formation in the presence of non‐extensive electron distribution. Issue 8 (23rd June 2021) - Moulick, Rakesh; Garg, Anuj; Kumar, Mukesh
Abstract: The main aim of this article is to recognize the sheath formation in the presence of non‐extensive electron distribution. The role of ion–neutral collision parameter K and the non‐extensive parameter " q " has been discussed. Existing literature suggests that the presence of non‐extensive electrons potentially modifies the plasma sheath behaviour. However, numerical calculations over the full plasma range, jointly addressing the sheath and presheath, are rare. Sheath formation, being a very fundamental phenomenon, deserves enough investigation in the region of non‐extensive distribution of particles. This study attempts to bridge the gap in understanding the formation of the sheath in collisional plasma in the light of both Boltzmann and q ‐distributed non‐extensive electrons.